ISDEV-UNISSA STRENGTHEN TIES THROUGH SOCIOACADEMIC LABORATORY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
GADONG, BRUNEI DARUSSALAM, July 2015 The existing ties and cooperation between the Centre for Islamic Development Management Studies (ISDEV), Universiti Sains Malaysia (USM) and Universiti Islam Sultan Sharif Ali (UNISSA), Brunei Darussalam was further strengthened through a joint academic programme called the ISDEVUNISSA SocioAcademic Laboratory Programme which began here on 27 July 2015.